2012
DOI: 10.3389/fmicb.2012.00372
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and nitrous oxide turnover in natural and engineered microbial communities: biological pathways, chemical reactions, and novel technologies

Abstract: Nitrous oxide (N2O) is an environmentally important atmospheric trace gas because it is an effective greenhouse gas and it leads to ozone depletion through photo-chemical nitric oxide (NO) production in the stratosphere. Mitigating its steady increase in atmospheric concentration requires an understanding of the mechanisms that lead to its formation in natural and engineered microbial communities. N2O is formed biologically from the oxidation of hydroxylamine (NH2OH) or the reduction of nitrite (NO−2) to NO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
217
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(223 citation statements)
references
References 227 publications
(374 reference statements)
5
217
0
1
Order By: Relevance
“…NO was produced in the upper 1 mm under oxic conditions, reaching a concentration of 0.13 mmol L 21 . The production of NO in the oxic zone, directly below the sediment surface, has also been observed previously with NO microsensors in marine, permeable sediments, where NO reached peak concentrations of 0.5 mmol L 21 when measured directly in the field and 0.9 mmol L 21 when measured in cores stored for 3 d at 4uC in the laboratory (Schreiber et al 2008). These previous results from marine sediments indicate that NO measurements in cores might overestimate net NO production occurring in the field, possibly due to an increased flux of Fig.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…NO was produced in the upper 1 mm under oxic conditions, reaching a concentration of 0.13 mmol L 21 . The production of NO in the oxic zone, directly below the sediment surface, has also been observed previously with NO microsensors in marine, permeable sediments, where NO reached peak concentrations of 0.5 mmol L 21 when measured directly in the field and 0.9 mmol L 21 when measured in cores stored for 3 d at 4uC in the laboratory (Schreiber et al 2008). These previous results from marine sediments indicate that NO measurements in cores might overestimate net NO production occurring in the field, possibly due to an increased flux of Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Sediment from the depth horizon between 0.5 and 1.5 cm was pooled and mixed at a 1 : 1 ratio with artificial freshwater medium (AFmedium; the composition of the medium is given in Schreiber et al [2009]) without any inorganic nitrogen and stored overnight at 4uC. On the following day, the overlying water was discarded, and the sediment was washed again with AF-medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two mainly N 2 O-yielding can explain the reason for the higher N 2 O production by AOB than AOA, NH 2 OH oxidation and nitrifier denitrification (Shaw et al 2006;Stein 2011;Schreiber et al 2012). It was reported that N 2 O emission from the oxidation of NH 2 OH contributed very little to total N 2 O production and nitrifier denitrification was believed to be the predominant process for N 2 O production in soils with 50 % < WFPS < 70 % (Kool et al 2010(Kool et al , 2011.…”
Section: Discussionmentioning
confidence: 99%